Young children's influence on family consumer behavior. Issue 4 (11th September 2017) - Bertol, Kátia Eloisa; Broilo, Patricia Liebesny; Espartel, Lélis Balestrin; Basso, Kenny
Abstract : Purpose: This study aimed to understand young children's influence on family consumer behavior by examining children's and parents' points of view in the Brazilian context. Design/methodology/approach: Through an exploratory approach, the study used focus group discussions and in-depth interviews. Specifically, to elicit children's perceptions, two focus groups were conducted, and to capture the perspective of the parents, 8 families, via 12 participants, were interviewed. Findings: Children's use of information provided by the media in their attempts to influence family decisions is perceived positively by parents because such behavior helps parents to fulfill their parental duties. Research implications: This study examines how young children perceive their influential role in family consumer decisions and how parents perceive this influence, given the existence of child adultization and adult infantilization. Originality/value: The findings extend the discussions regarding the adultization of children and the infantilization of adults, revealing positive aspects of such a trend in association with consumer behavior.